1996
DOI: 10.1002/(sici)1096-9071(199607)49:3<170::aid-jmv3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of adenovirus types 3 and 7 isolated from children with pneumonia in Beijing

Abstract: One hundred fifty strains of adenovirus sero-types 3 (Ad3) and 7 (Ad7) were analyzed. The viruses were isolated from patients, the majority of whom had pneumonia, from central and sub-urban Beijing over a 33-year period (1958-1990). Genomic analysis of DNA extracted from 74 strains of Ad3 and 76 strains of Ad7, with four to five restriction endonucleases (REs), revealed the presence of four and eight genome types, respectively: Ad3a2, Ad3a4, Ad3a5, Ad3a6 and Ad7p1, Ad7a1, Ad7a4, Ad7b, Ad7b1, Ad7d, Ad7d1, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Our results are similar to those of a previous study among children in China [10], in which HAdV-3 and HAdV-7 were the most identified serotypes. These results are also consistent with data from the United Kingdom [20], Canada [26], Korea [23], and Taiwan, China [27], in which species B was the most commonly identified HAdV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to those of a previous study among children in China [10], in which HAdV-3 and HAdV-7 were the most identified serotypes. These results are also consistent with data from the United Kingdom [20], Canada [26], Korea [23], and Taiwan, China [27], in which species B was the most commonly identified HAdV.…”
Section: Discussionsupporting
confidence: 91%
“…However, incidences of adenovirus-associated illnesses are higher among children than among adults. As such, in China, the impact of HAdVs on respiratory infection is well characterized in children [10][11][12][13][14][15] but not in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ad7h was the predominant genome type in the south cone of South America where it has circulated almost as the sole genomic variant of Ad7 since 1986 after substituting for genome type Ad7c (Kajon and Wadell, 1994;Kajon et al, 1996). In China, one genome type, Ad7d predominated for 10 years, between 1980and 1990(Li et al, 1996. In contrast, our results demonstrate that the prevalence of the Ad7d and Ad7l genome types alternated in Korea over the 10-year period between 1995 and 2004.…”
Section: Discussionmentioning
confidence: 51%
“…Various genome types and subtypes circulate in different countries and in different time period (Carballal et al, 2002;Gray et al, 2005;Kajon et al, 1996;Li et al, 1996). Adenoviruses with diverse genome types can cause outbreaks with various degrees of severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation